Qualitative gender analysis country report, Kenya: Building equitable climate resilient African bean and insect sectors - Oingo, Balentine; Ouya, Frederick; Wambua, Scholastica; Karanja, David; Lutomia, Cosmas; Ketema, Dessalegn; Nchanji, Eileen (2025)
This is a gender analysis of the Building Equitable Climate Resilient Africa Bean & Insect Sectors (BRAINS) project across five regions of Kenya. The project focuses on enhancing equitable climate resilience to improve food and nutrition security in Sub-Saharan Africa (SSA) among women, men, youth farmers, and entrepreneurs across the common bean, insect, and fruit tree value chains. The analysis collected data through age- and gender disaggregated focused group discussions with farmers and key informant interviews targeting persons with special needs (disability) and/or vulnerable groups, as well as entrepreneurs from the common bean, insect, and fruit tree value chains in the five regions. Based on the study objectives, the data were analysed in depth using content and thematic analysis. In the common bean, insect, and fruit tree value chains across Kenya’s different regions, distinct gender roles shape men’s and women’s participation across age groups. For instance, in the bean value chain, older women and young women typically focus on planting beans for household consumption or lower-value markets, while older men often cultivate high-value crops like fruit trees and beans to secure better market prices. Tasks are more equitably shared between older men and older women in the production of fruit trees, with older men focusing on initial farming activities and older women on management, value addition, and marketing. Young men and young women are primarily involved in the selling and transporting of fruits. Overall, older men are involved in strategic decisions and hold greater decision-making power in areas such as planting methods, crop management, market sales, and the use of income, compared to older women and youth. This gendered division of labour underscores the diverse roles and influences of each gender and age group within the agricultural process. Climate variability poses substantial challenges to the livelihoods of women and men alike in all regions. Droughts, heavy rains, pest infestations, and other climatic changes significantly impact crops and pollinators, reducing yields, causing food shortages, and leading to income losses. These challenges are compounded by gender norms that exacerbate the vulnerability of women (young and older), who often bear the brunt of agricultural work. Despite these challenges, farmers are increasingly adopting climate-resilient practices such as mulching, intercropping, organic farming, and agroforestry, supported by non-state organizations and government initiatives. The positive impact of social networks and collective action on advancing gender equality and community empowerment is evident. Efforts by NGOs and programs have empowered women to take on leadership roles, contributing significantly to agricultural practices and community development. Waste management practices employ diverse approaches to enhance soil health and sustainability, with older and young women primarily responsible for managing household and agricultural waste, thereby fostering community resilience. Financial opportunities and challenges significantly affect income and sustainability in bean, insect and fruit tree farming, highlighting the need for equitable access to financial services for all farmers. Access to financial services significantly benefits farmers by enhancing business operations and agricultural productivity, increasing profits and business growth. However, older women are generally more active in taking loans and are considered more trustworthy, often participating in table banking and self-help groups. On the other hand, older men and youth are more averse to financial risks and have limited access to financial support programs tailored specifically to them. Addressing these disparities and challenges requires targeted interventions to promote inclusivity and support sustainable agricultural development. The findings emphasise the critical importance of understanding gender roles and decision-making, climate change impacts, the role of social networks, waste management practices, access to financial services, and the potential for business growth across three value chains in Kenya’s five regions.